2019
DOI: 10.1186/s12955-019-1234-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the psychosocial screening instrument for physical trauma patients (PSIT)

Abstract: BackgroundEarly detection of psychosocial problems post-injury may prevent them from becoming chronic. Currently, there is no psychosocial screening instrument that can be used in patients surviving a physical trauma or injury. Therefore, we recently developed a psychosocial screening instrument for adult physical trauma patients, the PSIT. The aim of this study was to finalize and psychometrically examine the PSIT.MethodsAll adult (≥ 18 years) trauma patients admitted to a Dutch level I trauma center from Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Our study has implications for daily clinical practice. Clinicians with knowledge of risk profiles can identify and screen patients at an early stage in the ED or department of surgery (Levett & Grimmett, 2019 ) by using the Psychosocial Screening Instrument for Physical Trauma Patients (PSIT) (Karabatzakis, Den Oudsten, Gosens, & De Vries, 2019 ). HCPs could ask at-risk patients about their needs for additional care in the form of consultation from a social worker or health psychologist.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has implications for daily clinical practice. Clinicians with knowledge of risk profiles can identify and screen patients at an early stage in the ED or department of surgery (Levett & Grimmett, 2019 ) by using the Psychosocial Screening Instrument for Physical Trauma Patients (PSIT) (Karabatzakis, Den Oudsten, Gosens, & De Vries, 2019 ). HCPs could ask at-risk patients about their needs for additional care in the form of consultation from a social worker or health psychologist.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, HCPs’ contribution in care might affect patients’ recovery, because satisfaction with care could facilitate recovery. In order to predict who is at risk for psychological problems and disorders, patients can be screened almost directly after injury using the Injured Trauma and Survival Screen (ITSS) [ 60 ] or the Psychosocial Screening Instrument for physical Trauma patients (PSIT) [ 61 ]. Then, patients can be prevented from physical, psychological, and social consequences by providing early psychological treatment during hospitalization to improve patients’ wellbeing [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…A major strength and study implication is that it identified patients at risk for impaired QOL. This knowledge will help clinicians to screen patients in an early stage, for example, on the emergency department or department of surgery, by using the Psychosocial Screening Instrument for physical Trauma patients (PSIT) [ 56 ]. In addition, the trajectories seemed to be stable during 12 months after trauma.…”
Section: Discussionmentioning
confidence: 99%